2021
DOI: 10.1155/2021/6692811
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Binding Proteins as Potential Biomarkers for Chronic Inflammation-Induced Cancer Diagnosis and Therapy

Abstract: Actin-binding proteins (ABPs), by interacting with actin, regulate the polymerization, depolymerization, bundling, and cross-linking of actin filaments, directly or indirectly, thereby mediating the maintenance of cell morphology, cell movement, and many other biological functions. Consequently, these functions of ABPs help regulate cancer cell invasion and metastasis when cancer occurs. In recent years, a variety of ABPs have been found to be abnormally expressed in various cancers, indicating that the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 167 publications
(169 reference statements)
0
18
0
Order By: Relevance
“…Actin-binding proteins, which play roles in multiple biological activities such as cell movement, cytokinesis, and other biological processes [38], are closely associated with invasion and metastasis in tumor cells, DNA repair, and transcription regulation [39]. Multiple actinbinding proteins were verified to be aberrantly expressed in various tumors, and were attributed to tumor invasion and metastasis [40]. GSVA enrichment analysis of immune subcomponent types showed that they were enriched in aspects related to the immune response, including negative regulation of mast cell activation, and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Actin-binding proteins, which play roles in multiple biological activities such as cell movement, cytokinesis, and other biological processes [38], are closely associated with invasion and metastasis in tumor cells, DNA repair, and transcription regulation [39]. Multiple actinbinding proteins were verified to be aberrantly expressed in various tumors, and were attributed to tumor invasion and metastasis [40]. GSVA enrichment analysis of immune subcomponent types showed that they were enriched in aspects related to the immune response, including negative regulation of mast cell activation, and NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such a domain has never been considered as a drug target. Although not many AAP-targeting drugs are promising for clinical use, AAPs have the potential to be used as biomarkers for some diseases; for example, some AAPs are upregulated in certain cancers [130][131][132][133][134].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The dysregulation of multiple actin-binding proteins can also play a role in the inflammatory processes in tissues [159]. For example, the actin crosslinking protein fascin is overexpressed in inflammatory bowel disease and is involved in immune cell locomotion and mechanotransduction through the nuclear envelope [160,161].…”
Section: Actin-myosin Cytoskeleton and Cell Contractilitymentioning
confidence: 99%